SEPAK BOLA SEBAGAI INSTRUMEN PEMBANGUNAN EKONOMI DALAM ERA GLOBALISASI: PELUANG DAN TANTANGAN BAGI NEGARA - Achmad Muthiurrohman; Nuzulia Kumalasari; Halif (Jurnal Riset Multidisiplin Edukasi, 2025)
The increasing involvement of Indonesian investors in the ownership of European football clubs reflects a global transformation of football from a recreational sport into a highly lucrative industry. However, such investment activities operate within a dual regulatory landscape that combines national corporate law of the host country with transnational sports law (lex sportiva) governed by FIFA and UEFA. This study aims to analyze the legal protection afforded to Indonesian investors in European football club ownership and to identify the regulatory challenges arising from this intersection of legal systems. Using a normative juridical method supported by statutory, conceptual, and case approaches, this research examines international sports regulations, national legal frameworks, and investment agreements applicable to foreign ownership in European leagues. The findings indicate that various layers of legal protection exist, including UEFA financial sustainability rules, FIFA transfer regulations, bilateral investment treaties, and international arbitration mechanisms. Nonetheless, regulatory complexities, limitations on owner intervention, political–economic risk, and financial volatility of the football industry continue to create legal uncertainty. Therefore, comprehensive regulatory understanding and strong compliance strategies are essential to ensure the sustainability of investments while strengthening Indonesia’s presence and credibility in the global football industry.